Management of the Urban Infrastructure in Conditions of Reforming of the Public Authority in Ukraine: Theoretical Aspects - Haiduchenko, Svitlana; Maliukhova, Yuliya (Theory and Practice of Public Administration, 2019)
The article deals with theoretical aspects of the management system of the urban infrastructure. The scientific approaches to the term “infrastructure” are systematized that is interpreted as a complex of life vital for population objects of a territorial community. Determination of the content of management of the urban infrastructure gave a possibility to establish its components: objects, elements, principles, mechanisms, methods, approaches. The main objects of city management are considered as road, transport, energy, urban, industrial, engineering, communal, scientific, information and communication, social, trade, and cultural infrastructures. It is specified that each of the objects contains separate elements, in particular: enterprises, institutions, organizations, structures, institutions, territories and others. The city infrastructure elements include the normative base, budget, fiscal instruments, knowledge management, and others. Among the features of management of the urban infrastructure, in the context of reforming public authority in Ukraine, is defined: management competencies that are aimed at combining of the main components of the management system of the regional infrastructure in order to increase competitiveness of the region; implementation of the reform that requires a constant transformation of management bodies, management methods, improvement of managers’ qualification, etc. It is indicated that the infrastructure is a mechanism for increasing of the city’s competitiveness and contributes to the improvement of the economic component, strengthening of the managerial apparatus and activation of attraction of investments. The importance of the urban infrastructure grows in large cities. It is characterized by big investments and the need of constant maintenance.